GEOHYDROTHERMAL MODEL OF ARJUNO, WELIRANG AND PENANGGUNGAN VOLCANOES EAST JAVA, INDONESIA - Untung Sumotarto; F. Hendrasto; Wibagiyo Wibagiyo (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Trisakti, 2017)
Indonesia is a country having a high geothermal energy potential. The geothermal energy in Java island, as a volcanic row island, has been explored and produced. One of the area that has not been produced is volcanic area around Arjuno, Welirang and Penanggungan (AWP) located in East Java. Geochemical survey has been performed to explore a more detailed objective in exploring the potential resource of geothermal energy of this area. Chemical and isotopic analysis shows the maturity level of waters taken from water springs in the area. The immature water from the water springs is interpreted coming mostly from meteoric water which flows quite fast forming water springs around the area. Geohydrothermally, the water flows through porous and permeable volcanic rocks that receive heat from igneous rocks existing together in the area. The igneous rocks are flowing heat conductively from magma below the AWP volcanoes.